Sustainability Analysis of the Rural Agribusiness Development Program (PUAP) in Bangsri Village, Sukodono Sub-district, Sidoarjo Regency, East Java Province - Eva Noviana Maulanur Rohmah; Nuriah Yuliati; Risqi Firdaus Setiawan (Universitas Muhammadiyah Palembang, 2026)
The Rural Agribusiness Development Program (PUAP) is a government initiative aimed at improving access to capital for smallholder farmers. However, out of the 13 PUAP recipient villages in Sukodono sub-district, Sidoarjo Regency, East Java Province, only five villages are still implementing the program, with Bangsri village demonstrating the highest level of sustainability. This study aims to analyze the factors influencing PUAP sustainability in Bangsri village using a quantitative approach with 61 respondents. Data were collected through questionnaires and analyzed using the SEM-PLS method with the assistance of SmartPLS 4 software. This research was conducted from December 2024 to February 2025. The results indicate that Gapoktan management and government support have a positive and significant effect on program sustainability, whereas farmer capacity does not have a significant effect. government support, provided through training, mentoring, and monitoring, is the primary factor in maintaining PUAP sustainability, complemented by effective Gapoktan management in planning, transparency, and evaluation. These findings confirm that program sustainability depends more on institutional strength and external support than on individual farmers' abilities. The implications of this study suggest the need for increased assistance to farmers to optimize program utilization. Additionally, Gapoktan needs to strengthen its managerial capacity, particularly in terms of transparency and evaluation. Meanwhile, the government is expected to continue providing training, mentoring, and monitoring.